Co0.85Bi0.15Fe1.9X0.1O4 (X = Ce4+, Sm3+, Ho3+, and Er3+) Nanoparticles with Selective Anticancer Activity: A Structural and Morphological Approach - Liza Saher; Adel Benali; Saoussen Haddad; Essebti Dhahri; Manuel P. F. Graça; Benilde F. O. Costa; Luisa A. Helguero; Artur M. S. Silva (Crystals)
In this work, we synthesized the Co0.85Bi0.15Fe1.9X0.1O4 (X = Ce3+, Sm3+, Ho3+, and Er3+) nanoparticles via the auto-combustion method. The cell viability against two breast cancer cells (MDA-MB-231 and T-47D cells) and the PC3 prostate cancer cells were carefully analyzed and correlated with the structural parameters and particle size values as well as the chemical composition. The produced compounds’ morphological and structural characteristics were performed using scanning transmission microscopy (TEM) and X-ray Diffraction (XRD). For all compounds, the analyses of the XRD experimental data revealed a structurally reversed cubic spinel with space group Fd-3m. All of the compounds had crystallites smaller than 45 nm which concorded well with the particle size values deduced from TEM images. Co0.85Bi0.15Fe1.9Ho0.1O4 nanoparticles induced a high mortality of breast and prostate cancer cells (MDA-MB-231, T-47D, and PC3) while the Co0.85Bi0.15Fe1.9Sm0.1O4 compound (higher particle size) reduced almost 35% of MDA-MB-231 cancer cells. With very low cytotoxicity against normal human cells, the Co0.85Bi0.15Fe1.9Ho0.1O4 nanoparticles play a significant role in the elimination of cancer cells.